Did they go native? Representations of first encounters and personal interrelations with First Nations Canadians in the writings of Susanna Moodie and Catharine Parr Traill - Bigot, Corinne (The Journal of Commonwealth Literature, 2014)
International audience Between 1836 and 1852, Susanna Moodie and Catharine Parr Traill, two British gentlewomen who had emigrated to Canada, published accounts of their lives in the backwoods of Canada for a British audience. Descriptions of their encounters with their Native neighbours, more particularly women, are prominent in their texts. A gradual sense of intimacy permeates the writings, battling with the prejudices of the times.